Enterotoxin and Emetic Toxin Genes Profiles and Genetic Diversity of Bacillus cereus Isolated from Food, Environmental and Clinical Samples in Serbia - Dejana Savić; Elizabeta Ristanović; Biljana Miljković Selimović; Sonja Radaković; Dragana Jošić; Zorica Lepšanović (Acta Veterinaria, 2020)
Bacillus cereus, usually ingested by food, can cause two types of disease due to the presence of toxins: vomiting and diarrhea syndrome. Systemic infections can also occur. The aim was to detect genes for enterotoxins (hblA, entFM) and emetic toxin (cer) and to investigate the genetic heterogeneity of B. cereus isolates from food, environment and human stool. Identification of B. cereus was performed by means of selective medium, classical biochemical test and polymerase chain reaction (PCR). Toxin genes were detected by PCR. Typing was performed by random amplified polymorphic DNA (RAPD). EntFM gene was present in all stool and food samples and in 28/30 environmental isolates. HblA gene was present in 29/30 stool, 23/30 food and 24/30 environmental isolates. Cer gene was present in 30/30 stool, 28/30 food and 25/30 environmental isolates. The RAPD results show high heterogeneity among the isolates from each group. In the cumulative dendrogram, representative isolates from all three groups formed two clusters with a difference of 53%. The detection of toxin genes in all B. cereus isolates indicated these bacteria as potentially pathogenic and a serious threat for human health. The presence of isolates from all three groups in the same cluster suggests the existence of similar strains in the environment, food and patients, which is in line with the circulation of strains in nature through the food chain.